Kepuasan Pasien Terhadap Variasi Bahan Makanan di Rumah Sakit - Laksmi Karunia Tanuwijaya; Tiara Dian Novitasari; Eva Putri Arfiani; Yudi Arimba Wani; Dina Elok Wulandari (Universitas Muhammadiyah Semarang, 2019)
Food service at the hospital is being widely reported, especially with regard to patient satisfaction. There are several nutrition service factors that can affect patient satisfaction, one of them is a variation of food ingredients. The purpose of this study was to know the relationship between variations in the types of food ingredients with patient satisfaction. Type of researchwas a quantitative research using cross sectional design with population of adult patients at class 2 and 3 who received a regular or soft diet. The sampling method was convenience sampling. Total sample were 97 patients and using the questionnaire as data collection instrument. The results of data analysis using Spearman Correlation test showed that therewere a relation (p <0,05) between animal protein food ingredients variation (<0,001), vegetable protein food ingredients variation (<0,001), vegetable food ingredients (0,006), and overall food material variation (<0,001) against patients satisfaction. Based on the results of data analysis can be concluded that variety of food ingredients affect patients satisfaction. Keywords : hospital, variation of food ingredients, patients satisfaction